All‐oral, interferon‐free treatment for chronic hepatitis C: cost‐effectiveness analyses. Issue 12 (10th June 2013) - Hagan, L. M.; Yang, Z.; Ehteshami, M.; Schinazi, R. F.
Summary: Interferon‐based standard of care treatments (SOC) for chronic hepatitis C are unable to provide high cure rates in certain subgroups of the infected population and can cause debilitating side effects. Clinical trials evaluating all‐oral, interferon‐free treatments have demonstrated high rates of sustained virologic response with no resistance or major adverse events in most populations. As these drug regimens move towards FDA approval, it will be important to assess their cost‐effectiveness in addition to their clinical efficacy. A decision‐analytic Markov model with a lifetime, societal perspective was used to evaluate the cost‐effectiveness of a generalized all‐oral drug regimen compared to SOC by modelling the progression of a 50‐year‐old, HCV‐positive cohort through disease natural history and treatment. In base case analysis, all‐oral treatment dominated SOC across a range of willingness‐to‐pay (WTP) thresholds with an incremental cost‐effectiveness ratio (ICER) of US44 514/quality‐adjusted life year (QALY). In sensitivity analyses, the model was sensitive to all‐oral drug costs as well as rates of SVR and treatment uptake among noncirrhotic subjects, but robust to variations in all other parameters. All‐oral treatment was most cost‐effective among genotype 1 subjects but remained cost‐effective for genotypes 2 and 3 at WTP thresholds ≥80 000/QALY. Quality‐adjusted life years gained per dollar spent were maximized in younger treatment cohorts. Using this model, the degree of cost‐effectiveness depended on the WTP threshold and the final cost set for approved drug combinations.